2017
DOI: 10.1186/s12955-017-0661-5
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of alternative measures of functioning and wellbeing for adults with sickle cell disease: comparison of PROMIS® to ASCQ-Me℠

Abstract: BackgroundSickle Cell Disease (SCD) causes profound suffering and decrements in daily functioning. Demand is growing for valid and reliable measures to systematically document these effects, particularly in adults. The Adult Sickle Cell Quality of Life Measurement System, ASCQ-Me℠, was developed for this purpose. ASCQ-Me℠ is one of four measurement systems housed within the Person–Centered Assessment Resource (PCAR), funded by the National Institutes of Health, to support clinical research. To help users selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
84
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(87 citation statements)
references
References 90 publications
2
84
0
1
Order By: Relevance
“…The issue of chronic pain was difficult to address with the study design, as it seems highly likely that individuals with 40 pain events per year are experiencing chronic pain. However, self-reported VOC in SCD has also been useful as a clinical endpoint in drug trials, patient quality of life measures and as a prognostic marker for mortality (Platt et al , 1991, Charache et al , 1995; Keller et al , 2017; Machado et al , 2011; Hoots and Shurin, 2012). The possible poor definition of VOC is also tempered by its strong association with the use of health services, which was more objectively assessed; validating, to some extent, the use of such cost-effective patient reported outcomes for genetic association study.…”
Section: Discussionmentioning
confidence: 99%
“…The issue of chronic pain was difficult to address with the study design, as it seems highly likely that individuals with 40 pain events per year are experiencing chronic pain. However, self-reported VOC in SCD has also been useful as a clinical endpoint in drug trials, patient quality of life measures and as a prognostic marker for mortality (Platt et al , 1991, Charache et al , 1995; Keller et al , 2017; Machado et al , 2011; Hoots and Shurin, 2012). The possible poor definition of VOC is also tempered by its strong association with the use of health services, which was more objectively assessed; validating, to some extent, the use of such cost-effective patient reported outcomes for genetic association study.…”
Section: Discussionmentioning
confidence: 99%
“…Patient Reported Outcomes Measurement Information System (PROMIS) measures were also prospectively collected at the same time points in a subgroup of these patients ( n = 20). The PROMIS domains assessed included pain intensity, pain impact, anxiety, depression, satisfaction with social role, physical function, fatigue and sleep disturbance (Cella et al , ; Keller et al , ). All PROMIS raw data were converted to T‐scores.…”
Section: Pre‐ and One‐year Post‐hsct Patient Characteristics Includinmentioning
confidence: 99%
“…44,45 In adults, PROMIS Pain Interference was validated in adults with SCD in a comparative study with ASCQ-ME and was found to be sensitive to differences in the presence of clinical complications. 46 ASCQ-ME Pain Impact was shown to be valid 47 with regard to overall SCD severity, but its longitudinal validity is not yet established.…”
Section: Measuring Patient-reported Pain Outcomesmentioning
confidence: 97%
“…48,49 Pain Behavior and Pain Quality domains have been used in adults with SCD. 46,47 For assessment of pain behavior, the PROs panel recommends using the PROMIS Pain Behavior domain for children and adults with SCD.…”
Section: Measuring Patient-reported Pain Outcomesmentioning
confidence: 99%